Observations on some Avian Coccidia (Apicomplexa: Eimeriidae) in Amazonian Brazil - Lainson,Ralph (1994)
Oocysts of Eimeria porphyrulae n. sp. are described in faeces of Porphyrula martinica (Aves: Gruiformes: Rallidae). They are ellipsoidal to oval, 22.4 x 17.7 (20.0-23.7 x 16.2-18.7) µm, shape-index (length/width) 1.3. Oocyst wall about 1.25 µm thick, colourless, with two layers: inner one prominently striated. Micropyle and sub-micropylar granule present: no oocyst residuum. Sporocysts 17.5 x 9.0 (17.0-19.0 x 8.0-10.0) µm, shape-index 1.9, with inconspicuous Stieda/sub-Stieda bodies. Sporocyst residuum of scattered granules, sometimes a compact mass: sporozoites with two refractile bodies. Eimeria crypturelli n. sp. is described in faeces of Crypturellus soiu (Tinamiformes: Tinamidae). Oocysts ellipsoidal-oval, 20.75 x 14.5 (17.5-25.0 x 11.25-21.25) µm, shape-index 1.4. Oocysts wall about 1.25 µm thick and bi-layered: inner layer faintly striated. Micropyle present, with oocyst residuum immediately below: single polar body rarely present. Sporocysts 13.0 x 7.5 (12.5-13.75 x 7,5-8.1) µm, shape-index 1.7, with a Stieda body but seemingly no sub-Stieda. Sporocyst residuum compact: sporozoites with two refractile bodies. Isospora cacici n. sp. is recorded from faeces of Cacicus cela cela (Passeriformes: Icteridae). Oocysts subspherical-spherical, 26.5 x 23.7 (22.5-27.5 x 20.0-26.2) µm, shape-index 1.1. Wall a single, colourless layer about 1.5 µm thick. No micropyle or oocyst residuum: 1-2 polar bodies. Sporocysts ellipsoidal, 17.7 x 12.5 (17.5-18.75 x 11.25-13.75) µm, shape-index 1.4, with pronounced Stieda/sub-Stieda bodies: residuum compact and sporozoites with two refractile bodies. Isospora thraupis n. sp. is described from faeces of Thraupis palmarum melanoptera (Passeriformes: Thraupidae). Oocysts subspherial-spherical, 19.9 x 19.0 (18.7-21.2 x 18.75-20.0) µm, shape-index 1.0. Wall about 0.6 µm thick, smooth, colourless and a single layer: no micropyle, oocyst residuum or polar bodies. Sporocysts 14.2 x 9.2 (13.7-16.2 x 8.7-10.0) µm, shape-index 1.5: Stied/sub-Stieda bodies inconspicuous. Residuum compact: sporozoites with two refractile bodies.